QIYAS DAN ‘URF DALAM HUKUM ZAKAT ANTARA KONSEP DAN PRAKTIK - Bariyah, Oneng Nurul (Faculty of Islamic Studies, University of Muhammadiyah Jakarta, 2017)
This paper explains the position of qiyas and 'urf in the law of zakat both in concept and in practice. This is motivated by the idea that worship it is subject to the provisions of Shari'ah both the Qur’an and the Sunnah of the Prophet, there is no gap for ijtihad in it. However, it only happens in worship mahdhah, while the part of religious charity although there is space to do ijtihad. By analyzing the normative source of law, both the Qur'an and the Sunnah was found that qiyas and 'urf is very influential in determining the law of zakat. This is in line with the rules stipulate that the customs influential changes in law enforcement. Similarly, qiyas used in zakat going on in measures of the zakat for objects that are not explicitly mentioned in the Qur’an and the Sunnah of the Prophet as zakat of income. Qiyas and 'urf become the method of ijtihad development of charity law.